Dynamic Analysis of Physicochemical and Biochemical Indices and Microbial Communities of Light-Flavor Daqu during Storage. (2nd October 2019) - Liu, Penghui; Zhang, Lihong; Du, Xiaowei; Zhao, Jinglong; Gao, Gang; Zhang, Xiuhong
Abstract: To understand the influence of storage period on the quality of light-flavor Daqu, physicochemical and biochemical indices, as well as microbial communities of Daqu were analyzed by traditional and metagenomics methods. The results suggest that the moisture content of the Daqu samples are essentially invariant during the storage period; the acidity ascended slowly during the first 3 months, then descended; the saccharifying power of some samples began to decrease during the first 3 months. The diversity of the bacterial and fungal communities of some of the Daqu samples was found to decline to a minimum after storage for 3 months. On the basis of the variations in primary indices of the Daqu samples, it was deemed acceptable to store samples for 3 months before use for light-flavor Daqu. This is the first report of Daqu quality being estimated during storage by physicochemical, biochemical, and microbial indices, and it provides a theoretical foundation for the quality evaluation of Daqu during storage and use.